An exploration of work-life balance in generation Z who have just entered the workforce - Pelealu, Deasy Rinayanti (International Enterprise Integration Association, 2025)
Changing work patterns and increased awareness of mental health have driven attention to the issue of work-life balance (WLB), especially among Generation Z who are beginning to dominate the workforce. However, there is still a gap in understanding how this generation perceives and responds to the challenges of maintaining a balance between professional and personal life. This research aims to examine Generation Z's perceptions, challenges and adaptive strategies towards WLB through a systematic literature study approach. The method used involved searching scholarly articles from various accredited databases using relevant keywords, with selection based on specific inclusion and exclusion criteria. From the review of six key articles, it was found that Generation Z views WLB as a flexible integration of work and personal life, rather than a separation of time. They face challenges such as rigid conventional work culture, long working hours, digital pressures, and lack of mental health support. To overcome these, Generation Z employs strategies such as opting for flexible work, setting boundaries on work communication, and seeking out organizations that pay attention to employee well-being. These findings have important implications for organizations and policymakers in designing a more adaptive work system to support career sustainability and well-being of young people in the modern workforce.